Conservation techniques - Meixler, Marcia S; Bain, Mark B (Open textbook library., 2021)
This book fosters the recognition of options for making progress toward increased environmental conservation through an understanding of the underlying science and practice of a variety of conservation techniques. Today, there are expected benefits from integrated science and practice, and many people are promoting this as the way forward to improve our environment. Over time, trends emerge regarding the best way to conserve the environment, but so far an outstanding solution has not emerged. Each conservation technique has its foundational concepts, limitations, and implementation issues. Reviewing a collection of techniques provides a basis for considering which approach will be best for any specific environmental challenge. This book should advance the recognition of the challenges managing the environment, techniques that can be used to address the challenges, and the ways they might help foster the integration of science and the practice of ecological conservation. This book is intended for students and management professionals who might benefit from a vision and guiding path that leads toward achieving ecological conservation for the long-term. This book is unique in the Open Educational Resources (OER) space as it seeks to present a range of conservation techniques with differing science concepts and applications.